Fine-scale survey of intertidal macroalgae reveals recent changes in a cold-water biogeographic stronghold - Monteiro, Cátia; Pereira, Joana; Seabra, Rui; Lima, Fernando P. (Frontiers in Marine Science, 2022)
Global warming has been causing severe impacts on marine ecosystems, a notorious one being shifts in the geographical ranges of species. The north-western coast of the Iberian Peninsula is an especially interesting zone to study distributional shifts as it has a strong latitudinal thermal gradient, is influenced by the Canary upwelling system (which partially cancels coastal warming) and holds some of the most diverse macroalgae communities in Europe. Notably, it is within this region that many cold-water species, common in northern Europe, have their southernmost distribution refuge. Recent studies hypothesize that the environmental conditions may be nonetheless changing and already threatening this biodiversity hotspot. The main goal of this study was to carry out a fine-scale assessment of the distributional limits of several macroalgae in North-western Iberia, as well as identify possible population and range shifts using historical data (2001-2005) as reference. In addition, non-indigenous species were also surveyed. We also assessed if the regions of (i) Galicia, (ii) Northern Portugal, and (iii) Central Portugal displayed distinctive characters regarding macroalgae composition and abundance. We identified an increase in abundance of some non-indigenous macroalgae as well as a decrease in the abundance of some cold-water species. In the most severe cases, cold-water species were extirpated along hundreds of km. The compounded effect of the decrease in the abundance of cold-water species and the increase in the abundance of non-indigenous species is leading to the homogenization of macroalgae communities in north-western Iberia.